Study of capillary flow with application in loading of blood samples - Han, Wending. (2009)
Due to the wide range of applications of microfluidic devices, it is important to understand the characteristics of fluid flow in minute capillaries. In this study, analysis is done on surface-tension driven flow of liquid in a closed-end capillary. Capillaries of different diameters are used along with fluids with different viscosity. In addition, an initial discussion on nanofluids is also included to discuss how they affect viscosity and hence fluid flow. In this project, proportions of Glycerol to Di water of 2:1 and 4:1 and 6:1 mixtures were experimented on capillaries of diameter 300, 500 and 700ID. Silicon glue was used to achieve a closed-end capillary so as to induce a back pressure force. A CCD camera was used to capture the images of the fluid flow and MB-ruler was used to measure the displacement of the fluid. Parameters of the nanofluids such as viscosity and density were also taken and analyzed to address how the nanofluids affect the viscosity of the fluids. The results show that when a fluid has a higher viscosity, it reached a shorter final displacement in the same period of time, hence explaining the low velocity of higher viscous fluids. Also a capillary tube with a larger diameter had a shorter final displacement. Lastly, it can be seen that higher mass fractions of nanoparticles solution tend to result in unstable viscosity readings over a certain range of shear rate. Hence, it can be deduced that higher mass fractions of nanoparticles are unsuitable for capillary flow.